Supplementation of Foals with a Saccharomyces cerevisiae Fermentation Product Alters the Early Response to Vaccination - Eva Ronja Terpeluk; Jana Schäfer; Christa Finkler-Schade; Hans-Joachim Schuberth (Animals, 2024)
Feed supplements supporting animal welfare and performance are becoming increasingly important. Immunomodulatory effects of such products have been observed in many species. The aim of this study was to analyze whether food supplementation with a Saccharomyces cerevisiae fermentation product (SCFP) affects the occurrence of foal diarrhea in early life, and whether the SCFP feeding has an impact on the immediate response to a parenteral vaccination at the age of 6–9 months. Eleven foals received the SCFP (OLI) and eleven foals were fed a placebo (PLA) for 29 days. Growth, diarrhea, and diarrhea severity were observed until day 30. After weaning, at the age of 6–9 months, foals were vaccinated parenterally against influenza and tetanus. The supplementation had no statistically significant effect on diarrhea duration and severity. On the day of vaccination, PLA and OLI foals did not differ significantly regarding numbers of circulating blood leukocyte subsets. However, the response to vaccination differed significantly between OLI and PLA foals. In OLI foals, the numbers of the major leukocyte fractions (granulocytes, lymphocytes, monocytes, CD4+ T cells, CD8+ T cells, CD21+ B cells, and MHC-II+/CD21− cells) increased significantly 24 h after vaccination but remained unchanged in PLA foals. The observed results suggest that early life supplementation with an SCFP may affect the early immune response to an initial vaccination.